Broadening Partnership for Strengthening the Networks of Politani Kupang - Stormy Vertygo; Steven Starmans; Albertien Kijne; Eurídice Leyequién; Dina V. Sinlae; Melinda R.S. Moata; Noldin Abolla (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2022)
A tailor-made training (TMT) assembled by both Politeknik Pertanian Negeri Kupang (Politani Kupang) and Van Hall Larenstein of Applied Sciences, Netherlands (VHL) was conducted from the 9th to 13th November 2020. This training focused on the importance of establishing, maintaining, and broadening partnerships for a better institutional development. As many as 19 participants were invited to attend the training and were assigned into ﬁve groups based on the ﬁve prioritized commodities the institution was planning to expand further, which were: meat/beef, coﬀee, honey, shallot, and catﬁsh. The training was organized through both online and oﬄine methods. The online method implemented both an asynchronous pathway, in which all the materials were posted through Google Classroom and Whatsapp group, and an asynchronous pathway, in which the teaching-learning process was organized via ZOOM. For the in-person method, the participantswere taken to a ﬁeld trip. By the end of the training, all the participants had understood the concepts of partnerships and their importance, how to construct and diﬀer between a Memorandum of Understanding (MoU) and a Contract, how to achieve cultural awareness for a fruitful partnership, and how to outline a business plan and demonstrate a 3-minute pitch to be implemented on potential business partners during the ﬁeld trip.